Enhancing Customer Satisfaction: The Impact of Service Quality and Store Atmosphere on Shopping Convenience - Putri, Shintania Camila; Lusianti, Dina; Wismar’ein, Dian (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This research aims to analyze how service quality and store atmosphere impact customer satisfaction, with shopping convenience as an intervening variable in Supermarket customers in Kudus, Indonesia. This research is quantitative, involving hypothesis testing. The sample for this study consisted of 144 respondents. The sampling technique used is non-probability sampling with a purposive sampling method. Data was collected using a questionnaire distributed via Google Forms. The instrument tests conducted include validity tests, reliability tests, and normality tests. The analysis technique used is SEM (Structural Equation Modeling) with AMOS 24 software. The results of this study indicate that service quality does not affect customer satisfaction, store atmosphere has no effect on customer satisfaction, service quality has no effect on shopping convenience, store atmosphere has a positive and significant effect on customer satisfaction, and shopping convenience has a positive and significant effect on customer satisfaction.